The Impact of Accounting Information Users’ Interests on Company’s Financial Accounting Policy Choice - Rudžionienė, Kristina (Ekonomika, 2004)
A company is a part of a wider social system: the entity is assumed to be influenced by, and in its turn to have influence upon, the society in which it operates. Thus, a company should attend to the expectations of particular users of accounting information in order to satisfy all or only main users’ interests to get information for their decision-making. The choice of the company’s financial accounting policy is a way to manipulate the users’ decision making. It is empirically tested that interests of accounting information users motivate to choose income increasing financial accounting policy. The most important users of accounting information are customers, suppliers, employees, capital providers, regulators, all users, foreign customers and suppliers. It is assumed that different groups of accounting information users are interested in special company’s determinants which influence company’s financial accounting policy choice. The main determinants in which the company’s users of accounting information are interested include research and development costs, advertising costs, financial leverage, pension schemes, auditing, level of inventory, return on assets, sales, etc. Empirical research in Lithuanian companies showed that when choosing financial accounting policy companies do not take into account interests of most users of accounting information, except regulators and capital providers. interests of regulators are expressed through rules of taxation in financial accounting practise. Respondents believe that when choose financial accounting policy managers of Lithuanian companies mostly respect the interests of shareholders, regulators, employees and respect least the interests of the media and the whole community. The position of small and medium companies does not greatly differ from the position of sample companies, but large companies find the shareholders’, regulators’, and media’s interests more important. It shows that large companies respect the interests of external users of accounting information when choosing financial accounting policy, but it is impossible to understand exactly in which direction these interests are shifted: income increasing or income decreasing.